Studi Kasus Kemampuan Pemecahan Masalah Matematis Materi Perbandingan di Kelas VIII Mts As-Syuhada - Vidya Ardhita Septiani (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study is designed to describe students' mathematical problem-solving skills in the topic of ratios, classified based on high, medium, and low ability levels. A qualitative approach is applied through a case study method. The subjects consist of three eighth-grade students from MTs Asy Syuhada in one class, selected based on their mathematics test scores, each representing high, medium, and low ability categories. The research instruments include two contextual questions on ratios and an interview guide. The evaluation of mathematical problem-solving skills is based on Pólya's stages, namely understanding the problem, devising a solution plan, executing the plan, and reviewing the answer. The research findings reveal that high-ability students successfully grasp and execute problem-solving effectively, although they are not always consistent in writing down the plan or reviewing the answers. Medium-ability students can understand the problem but still face difficulties in the planning stage and accuracy in interpreting instructions. Meanwhile, low-ability students are unable to devise a plan or solve the problem due to their weak mastery of ratio concepts. This research confirms that mathematical problem-solving skills are influenced by conceptual understanding, precision, and the habit of applying problem-solving steps systematically.